"Quality of Life in Epidermolysis Bullosa" and "Epidermolysis Bullosa Burden of Disease": Italian translation, cultural adaptation, and pilot testing of two disease-specific questionnaires - May El Hachem; Andrea Diociaiuti; Giovanna Zambruno; Tonia Samela; Francesca Ferretti; Claudia Carnevale; Renata Linertová; Christine Bodemer; Dédée F. Murrell; Damiano Abeni (BMC, 2024)
Abstract Background Inherited epidermolysis bullosa (EB) is a clinically and genetically heterogeneous group of skin fragility disorders characterized by blister formation following minor trauma. Four major types are distinguished based on the level of cleavage within the skin. Most EB forms present severely disabling cutaneous and systemic signs and symptoms. Management relies on daily time-consuming and distressing topical medications, and symptomatic treatment of systemic findings. Disease manifestations, symptoms, and daily care strongly affect patient and caregiver quality of life (QoL). To date, there are two validated EB-specific questionnaires, the "Quality of Life in Epidermolysis Bullosa" (QOLEB) and the "Epidermolysis Bullosa Burden of Disease" (EB-BoD) for the evaluation of patient and family disease burden, respectively. The aim of our study was to develop an Italian translation of the two questionnaires and to pilot-test them. Methods The guidelines for translation and cross-cultural adaptation of health-related QoL measures were followed. Initially, two separate translations were generated for each questionnaire, and subsequently reconciled by an expert committee. This was followed by a back-translation process. The original texts and all translations underwent revision by the expert committee, resulting in definitive versions. The final versions were then tested in a pilot study involving cognitive debriefing in a group of 17 families, representative of all EB major types. Results The translation and reconciliation process led to minor changes to obtain semantic/idiomatic/cultural equivalence of the Italian versions with the original ones and to reconcile the questions with the answer options. The cognitive debriefing process showed a good understanding and did not require text modifications. Conclusions The Italian versions of the QOLEB and EB-BoD provide valuable tools in everyday clinical practice of reference centers, and they allow the participation in multicenter international real-life observational studies as well as in controlled clinical trials. They enable the identification of disease-specific psychological and socioeconomic challenges for EB patients and their families, guiding targeted interventions to ensure appropriate and timely care.